Application of User-Centered Design Method in E-Commerce Sales System - Amanda, Retno Tri; Putri, Raissa Amanda (Sistemasi: Jurnal Sistem Informasi, 2024)
E-commerce is the activity of buying and selling goods or services carried out electronically via the internet, involving online transaction, payment and delivery processes. The Azzahra Hijab Medan Shop is one of the shops engaged in selling hijabs in Medan City which still uses a conventional shop model without utilizing e-commerce to support the sales system. The transaction process in this shop is still done manually, from customers selecting goods to recording transactions in a book. Customers from outside the area can place online orders via the WhatsApp service with the shop owner providing a product photo catalog in stages. Therefore, an e-commerce system is needed to support online sales. The User Centered Design (UCD) method is important in designing e-commerce, starting with involving the user context in the early stages of development and involving system testing, enabling the creation of an optimal and user-friendly design. With the implementation of this E-Commerce based sales system, it is hoped that it will facilitate sales with more efficient transactions, faster data processing, help sales of goods become more accurate, and make it easier for consumers to order products.